LOCAL PERCEPTION OF THE DEGRADED LAND IMPACT - Sulistya Rini Pratiwi; Yohanna Thresia Nainggolan; Meylin Rahmawati (Journal of Applied Economics in Developing Countries, 2023)
This study aims to determine the perceptions of the farmers about the degraded land impact in Tarakan City. The study was conducted at the agricultural center, Juata Permai Village. This study was a descriptive study using a qualitative approach. The data collection used was by questionnaire and in-depth interviews. The result calculation of the score related to the farmers’ understanding of the degraded land impact was not-good. This showed that the level of knowledge and understanding of the farmers about the degraded land impact is low. In terms of the government’s responses, obtained an average of 31.37 and the not-good category. This suggested that the government prevention policy was relatively not effective and tended to be less informative. Overall, this showed that the farmers' appreciation for the improvement of degraded land belonged to agree category.